Investigation of the economic impact of surgical site infection development in cardiovascular surgeries on the prospective payment system in Japan - Ohno, Minoru; Shimada, Yosuke; Satoh, Masaya; Endoh, Daisuke; Amano, Atsushi; Hori, Satoshi (International Journal of Infection Control, 2019)
The purpose of this study was to evaluate the economic burden of surgical site infections (SSIs) that are included in the category of clean operation in the field of cardiovascular surgery. In total, 2,583 patients who underwent cardiac surgeries at Juntendo University Hospital in Japan between April 2008 and March 2018 were investigated. Among them, 9 SSI cases were individually matched to non-SSI cases based on a combination of age group (in 5-year increments), gender, timing of hospitalization (in 2-year intervals), National Healthcare Safety Network (NHSN) Risk Index, main disease category, and length of stay (LOS) prior to surgery (with the difference of ≤2 days). SSI and non-SSI cases were compared in terms of median LOS and piecework reference cost (PRC). The median LOS was 30 days for SSI cases and 19 days for non-SSI cases (p<0.05). The median PRC was 1,257,630 Japanese Yen [JPY] for SSI cases and 884,720 JPY for non-SSI cases (p<0.05). This study demonstrated that the development of SSIs significantly extended LOS and increased excess treatment costs. However, since the current Japanese prospective payment system, the Diagnosis Procedure Combination (DPC)-based payment system is calculated on daily basis, it was suggested that in some cases it may be more beneficial to keep a certain LOS than to inhibit SSI episodes with an aim to shorten LOS. It was also found that in hospitals with relatively shorter LOS, deemed benefit may be reduced in certain diagnosis-related groups. This may result in discouraging the prevention of SSIs.